Developing SMART Goals for Your Organization - Henry M. Cothran; Allen F. Wysocki (EDIS)
Individuals may set goals to achieve a personal objective such as career advancement. This publication is designed to introduce a sequential process for setting goals. It begins by defining a goal and identifying reasons for setting goals. It then describes a process based on the acronym SMART for developing and implementing goals. This document is FE577, one of a series of the Food and Resource Economics Department, UF/IFAS Extension. Original publication date November 2005.